Музична творчість в архівних документах - Рачковська, О. (Архіви України, 2009)
There is a characteristic of private sands of Ukrainian composers that are store in the Central state archive-museum of literature and art of Ukraine given in this archive. Musical heritage of 19–20 century are mention in this archive. Special attention is paid to the necessary of little know compositions, popularization in the multiple volume additions, materials concerning of National union of Ukraine composers.